2022
DOI: 10.2196/37484
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patients With Heart Failure Who Are Susceptible to De Novo Acute Kidney Injury: Machine Learning Approach

Abstract: Background Studies have shown that more than half of patients with heart failure (HF) with acute kidney injury (AKI) have newonset AKI, and renal function evaluation markers such as estimated glomerular filtration rate are usually not repeatedly tested during the hospitalization. As an independent risk factor, delayed AKI recognition has been shown to be associated with the adverse events of patients with HF, such as chronic kidney disease and death. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…More advanced machine-learning techniques, such as large language models (LLMs) and chatbots, have emerged recently [24]. Chatbots are AI systems designed to simulate human conversation audibly or with text-based tools [25][26][27]. Integrating these AI and machinelearning approaches into the study of HF and AKI has yielded encouraging outcomes.…”
Section: Ai and Machine Learning In Hf And Akimentioning
confidence: 99%
See 2 more Smart Citations
“…More advanced machine-learning techniques, such as large language models (LLMs) and chatbots, have emerged recently [24]. Chatbots are AI systems designed to simulate human conversation audibly or with text-based tools [25][26][27]. Integrating these AI and machinelearning approaches into the study of HF and AKI has yielded encouraging outcomes.…”
Section: Ai and Machine Learning In Hf And Akimentioning
confidence: 99%
“…Furthermore, while in-hospital mortality was observed to be higher in the high-risk group, the specific causes of death were not reported. Hong et al [26] highlighted the significant potential of unsupervised machine learning in patient risk stratification. Their innovative approach shed new light on identifying high-risk HF patients, underscoring the critical role of data-driven phenotyping in risk assessment.…”
Section: Unsupervised Machine Learning To Assess Aki Risk Among Patie...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted on the use of artificial intelligence (AI) in ESRD and CKD. [20,[25][26][27][28][29] However, these studies mostly focused on CKD prevention or identification. [21,[30][31][32][33] For mortality prediction in ESRD patients, most studies have focused on populations with only kidney transplant therapy or hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Correct clinical decision making relies on early risk assessment and diagnosis ( 10 ). Thus, it is clinically important to properly assess the risk factors for kidney injury in patients with CHF in an appropriate clinical context ( 11 ). Previous studies have shown that vascular disease, thiazide diuretic use, baseline blood urea nitrogen >9 mmol/L ( 12 ), elevated sCr on admission, a poor New York Heart Association (NYHA) classification of cardiac function ( 13 ), a medical history of chronic kidney disease (CKD), spironolactone exposure, and higher doses of loop diuretics ( 14 ) are independent risk factors for kidney injury in patients with CHF.…”
Section: Introductionmentioning
confidence: 99%